Economic Returns to Herbicide Resistance Management in the Short and Long Run: The Role of Neighbor Effects. Issue Volume 64: Issue SP1(2016) (September 2016) - Livingston, Michael; Fernandez-Cornejo, Jorge; Frisvold, George B.
Abstract : A bioeconomic model is used to estimate how managing glyphosate resistance to horseweed affects short- and long-run profits in corn, soybean, and corn-soybean rotation systems. Model results found that resistance management reduces profits in the first year of implementation, but increases profits in the second and subsequent 18 yr. In all three systems, long run gains begin to outweigh short-run costs (and resistance management "pays for itself") by the second year. Over a 20-yr horizon, the estimated annual average profit advantage from managing resistance exceeded $158 ha –1 ($64/acre) for corn, $137 ha –1 ($55/acre) for corn-soybean, and $55 ha –1 ($22/acre) for soybean. Seed immigration from a neighbor's field can reduce these gains, but this reduction is negligible if the neighbor also practices resistance management. If the neighbor did not manage resistance, however, the grower's estimated annual profit advantage fell to roughly $123 ha –1 ($50/acre) for corn, $60 ha –1 ($24/acre) for the corn-soybean rotation, and virtually zero for soybean. Methods applied in this study identify corn and corn-soybean rotations as cases where resistance management "pays for itself' quickly and significantly, even if the neighbor does not manage resistance. Continuous soybean presents a more challenging case that may require additional programs and incentives to encourage collective resistance management among growers. Even for continuous soybean, however, joint grower–neighbor resistance management can pay for itself within 2 yr.